Midwifery hurdles: Navigating tuberculosis screening challenges in South Africa - Violet M. Chewe; Sisinyana H. Khunou (AOSIS, 2024)
Background: In South Africa, screening for tuberculosis during pregnancy is a serious challenge. Tuberculosis is one of the leading indirect causes of mortality in pregnant women. Objectives: The objective of the study was to explore the challenges experienced by midwives regarding tuberculosis in pregnant women. Method: A qualitative exploratory research method was used to conduct the study. The study population comprised midwives who worked at primary healthcare clinics in the selected local area, Capricorn District, Limpopo province. Purposive non-probability sampling was used to select 10 participants. Data from participants were acquired using in-depth individual semi-structured interviews. Data analysis was carried out using manual thematic analysis following Tesch's technique. Results: The outcomes of this study included midwives knowing their roles regarding tuberculosis screening among pregnant women. They further highlighted their challenges while screening tuberculosis in pregnant women, such as shortage of screening tools, withholding of tuberculosis information, and language barrier. Conclusion: Midwives should have the necessary equipment and be trained in various languages used in the province to improve tuberculosis screening among all pregnant women. Contribution: Infected pregnant women and their unborn children's health can be improved by tuberculosis screening.